Reading Urban Spaces by the Space Syntax Method: A Proposal for the South Halic Region - Onder, Deniz Erinsel; Gigi, Yildirim (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
For a designer-architect to be able to make accurate predictions for any particular urban space, he/she needs to know the development stages of the city, as well as the city's various features across time. Thus, it is necessary to read the different segments that constitute the city to reveal its historical, cultural, social, physical and symbolic features. The aim of this study is to determine the social and physical problems of a historical urban space and subsequently to introduce physical and functional suggestions to improve the identified problems, and for the development of the area. The South Halic Area was chosen as a work-space because of its special importance in protecting the historical and cultural heritage found there and transferring it to future generations. With this in mind, in addition to literature studies, on-site observations and interviews, the area has been analyzed and evaluated using the space syntax method. The suggestions developed for the identified problems and solutions have been re-analyzed, and both the present data and the data obtained after the suggestions have been examined and the results have been presented.
Keywords: Reading space; space syntax; The South Halic Region; LEGIBILITY; Architecture